THE VITAMIN D HORMONE: A MULTITUDE OF ACTIONS POTENTIALLY INFLUENCING THE PHYSICAL FUNCTION DECLINE IN OLDER PERSONS - Cesari, Matteo (Geriatr Gerontol Int, 2010)
Vitamin D, a secosteroid (pro)-hormone, has been traditionally considered as a key regulator of bone metabolism, and calcium and phosphorous homeostasis through a negative feedback with the parathyroid hormone. However, during the last twenty years, the role played by vitamin D has been largely revised by recognizing it a pleiotropic action on a wide spectrum of systems, apparati, and tissues. Thus, vitamin D has growingly been involved as a primary determinant of biological modifications and specific clinical conditions. The effect of vitamin D on skeletal muscle and related outcomes (including physical function decline and disability) is surely one of the most relevant to study in the context of global aging. In the present review, the subclinical and clinical consequences of vitamin D deficiency/insufficiency, extremely frequent conditions in older age, are described. Special focus is given to skeletal muscle and physical function. Limitations of available scientific evidence on the topic are also discussed.